2005
DOI: 10.1038/sj.leu.2404023
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming MDR-associated chemoresistance in HL-60 acute myeloid leukemia cells by targeting shingosine kinase-1

Abstract: We examined the involvement of sphingosine kinase-1, a critical regulator of the sphingolipid balance, in susceptibility to antineoplastic agents of either sensitive or multidrugresistant acute myeloid leukemia cells. Contrary to parental HL-60 cells, doxorubicin and etoposide failed to trigger apoptosis in chemoresistant HL-60/Doxo and HL-60/VP16 cells overexpressing MRP1 and MDR1, respectively. Chemosensitive HL-60 cells displayed sphingosine kinase-1 inhibition coupled with ceramide generation. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
186
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(195 citation statements)
references
References 38 publications
6
186
1
2
Order By: Relevance
“…Recently, sphingosine kinase-1 (SPK1), the enzyme that phosphorylates sphingosine to form sphingosine-1-phosphate (S1P), could be activated by a number of growth factors and intracellular oncoproteins, and has been proven to be involved in signal transduction (Duan et al, 2004;Granata et al, 2004;Wattenberg et al, 2006). SPK1 activation is involved in the multistep progression and multidrug resistance of leukemia (Le Scolan et al, 2005;Bonhoure et al, 2006). Here, we show that SPK1 signal is also involved in the pathological progression of CML.…”
mentioning
confidence: 88%
“…Recently, sphingosine kinase-1 (SPK1), the enzyme that phosphorylates sphingosine to form sphingosine-1-phosphate (S1P), could be activated by a number of growth factors and intracellular oncoproteins, and has been proven to be involved in signal transduction (Duan et al, 2004;Granata et al, 2004;Wattenberg et al, 2006). SPK1 activation is involved in the multistep progression and multidrug resistance of leukemia (Le Scolan et al, 2005;Bonhoure et al, 2006). Here, we show that SPK1 signal is also involved in the pathological progression of CML.…”
mentioning
confidence: 88%
“…SphK1 mRNA content was found elevated in various human (9,10) and rodent tumor tissues (11). On the contrary, SphK1 down-regulation has been associated with cell death induced by anticancer treatments (6,8,12).…”
Section: Introductionmentioning
confidence: 94%
“…A key regulator of this balance is sphingosine kinase-1 (SphK1), which phosphorylates sphingosine (the catabolite of ceramide) to generate S1P, because it reduces proapoptotic ceramide levels by driving the sphingolipid metabolism toward antiapoptotic S1P. Accordingly, SphK1 overexpression promotes survival in response to stresses that increase ceramide content (6,8). SphK1 mRNA content was found elevated in various human (9,10) and rodent tumor tissues (11).…”
Section: Introductionmentioning
confidence: 99%
“…SphK1 mRNA content was found elevated in cancers, such as lung cancer, glioblastoma and colon carcinoma (Johnson et al, 2005;Van Brocklyn et al, 2005;Kawamori et al, 2006). On the contrary, down-regulation of SphK1 could arrest cell cycle and induce apoptosis (Pchejetski et al, 2005;Bonhoure et al, 2006;Cuvillier et al, 2007). Moreover, it has been shown that SphK1 impairs the efficacy of chemotherapy in prostate adenocarcinoma cells (Pchejetski et al, 2005).…”
Section: Introductionmentioning
confidence: 99%